2005
DOI: 10.1002/jcb.20524
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of regucalcin on cell differentiation and mineralization in osteoblastic MC3T3‐E1 cells

Abstract: The role of regucalcin in the regulation of osteoblastic cell function was investigated. Osteoblastic MC3T3-E1 cells with subconfluent monolayers were cultured in a medium containing regucalcin (10(-10)-10(-8) M) without fetal bovine serum (FBS). The proliferation of osteoblastic cells was not significantly altered in the presence of regucalcin. The results of reverse transcription-polymerase chain reaction (RT-PCR) analysis with specific primers showed that the expression of Runx2 (Cbfa1) and insulin-like gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 42 publications
(32 reference statements)
4
22
0
Order By: Relevance
“…Over-expression of RGN in the rat hepatoma cell line H4-II-E was shown to suppress the expression of oncogenes c-myc, Haras, and c-src, and increase the expression of tumor suppressor genes p53 and Rb [23,24]. Recent studies in hepatoma cell lines also showed growth suppression effects by RGN [25,26]. Therefore, upregulation of RGN may provide the benefit of suppressing hepatocarcinogenesis in Sod1−/− mice, whereas reduced expression of RGN may have the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of RGN in the rat hepatoma cell line H4-II-E was shown to suppress the expression of oncogenes c-myc, Haras, and c-src, and increase the expression of tumor suppressor genes p53 and Rb [23,24]. Recent studies in hepatoma cell lines also showed growth suppression effects by RGN [25,26]. Therefore, upregulation of RGN may provide the benefit of suppressing hepatocarcinogenesis in Sod1−/− mice, whereas reduced expression of RGN may have the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
“…Regucalcin has been demonstrated to stimulate osteoclast-like cell formation in mouse marrow culture in vitro, and the protein stimulates bone resorption in rat femoral tissue in vitro (34). Also, regucalcin is found to have suppressive effects on cell differentiation and mineralization in osteoblastic MC3T3-E1 cells in vitro (35).…”
Section: Regulatory Effect Of Exogenous Regucalcin On Cell Function Imentioning
confidence: 99%
“…Osteoblastic cell formation from bone marrow cells has been enhanced in regucalcin transgenic rats (36). Exogenous regucalcin has been shown to have stimulatory effects on osteoclastogenesis in bone marrow cell cultures (32) and suppressive effects on osteoblastic differentiation and mineralization in vitro (33). Regucalcin may play an important role in the regulation of bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous regucalcin in osteoblastic cells has suppressive effects on cell function that is involved in differentiation and mineralization (33). If regucalcin mRNA expression is regulated by various hormones and cytokines which are involved in the regulation of osteoblastic cell function, the endogenous regucalcin may be partly related, in light of hormone and cytokine effects on osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation